INFLUENCE OF PERCEIVED USEFULNESS, TRUST, PERCEIVED EASE OF USE AND SOCIAL INFLUENCE ON E-WALLET ADOPTION IN GENERATION Z - Melva Hermayanty Saragih; Marco Christian Mulyadi (Suluh Adiluhung Publisher (SAPub), 2025)
The purpose of this study was to analyze the factors that influence e-wallet adoption, including perceived usefulness, trust, perceived ease of use, and social influence. The research method is a quantitative method with data collection through a 1–5-point Likert scale questionnaire. The population of the study was Gen Z living in South Tangerang. The sampling technique was carried out using nonprobability sampling with a purposive sampling type. Respondent data in the study were obtained from 130 people and analyzed using multiple linear regression through the SPSS application. The results showed that perceived usefulness, trust, perceived ease of use, and social influence had a significant influence on e-wallet adoption. Social influence is the factor with the greatest influence on e-wallet adoption.